RESOLUTION OF XII CONGRESS OF RUSSIAN CHILDREN'S INFECTIOLOGISTS «ESSENTIAL ISSUES OF INFECTIOUS PATHOLOGY AND VACCINATION», 11-13 th December 2013, Moscow - статья Редакционная (LLC "Diagnostics and Vaccines", 2015)
.